1994
DOI: 10.1002/mrc.1260320705
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium and 18O isotope effects on 13C chemical shifts of sterically hindered and/or intramolecularly hydrogen‐bonded o‐hydroxy acyl aromatics

Abstract: A series of sterically hindered 0-hydroxy aromatic ketones were synthesized, including benzeae, naphthalene, pbeoanthene and pyrene derivatives. Deuterium isotope effects on the 13C chemical shifts of 2-hydroxy-l-acenaphthone and other sterically hindered, intramolcularly hydrogen-bonded aromatic ketones (OH exchanged) are shown to he M U S U~~. The two-bond isotope effects are very large. Likewise are the istope eff& on C-0, C-1, C-3 a d C-4 carbon resonances and some show unltsual signs. These unusual effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…5) revealed that cis the data for benzene derivatives and oleÐnic compounds fall on di †erent correlation lines, possibly with that of 1,2-disubstituted naphthalenes (4,5,18,23,25) in between. The data point of 2,3-disubstituted naphthalene (24) falls on the benzene derivative line.…”
Section: Resultsmentioning
confidence: 94%
“…5) revealed that cis the data for benzene derivatives and oleÐnic compounds fall on di †erent correlation lines, possibly with that of 1,2-disubstituted naphthalenes (4,5,18,23,25) in between. The data point of 2,3-disubstituted naphthalene (24) falls on the benzene derivative line.…”
Section: Resultsmentioning
confidence: 94%
“…3 For systems in which oxygen is the acceptor, it is relevant to study 17O chemical shifts to add to the information available from OH 1H chemical shifts,4 n*C(YD) (Y \ O),2,3,5h8 1*N(D)2 (Y \ N) and 1*13C(18O) (X \ C) isotope e †ects. 9 Hydrogen bonding has been shown to inÑuence Cx17O chemical shifts,10h25 and the e †ect has been described in terms of the acidity of the donor,23 the basicity of the acceptor,23 a twist of the acceptor group16 and in-plane distortions. 17,18 The OH chemical shifts of intramolecularly hydrogen-bonded phenols vary somewhat, 14,17,19h21 and recent data for indane-1, 3-diones show larger variations in enols.…”
Section: Introductionmentioning
confidence: 99%
“…18 In Schiff base N-oxides 1-4 in solution, a fine balance is expected between the structure that optimizes the strength of the hydrogen bond and that minimising the steric strain. Following the explanation given by Hansen et al, 11 we may suppose that a substitution of proton by deuterium leads to changes in the torsional angles in the seven-membered chelate ring, i.e. an increase in the nonplanarity of the molecule.…”
mentioning
confidence: 99%
“…9 An exception is sterically hindered compounds, in which an unusually large two-bond isotope effect 2 C-2(D) was observed. 10,11 If the proton transfer takes place, the deuterium isotope effect on 13 C-2 chemical shifts depends on temperature and the position of the equilibrium. We measured the two-bond and long-range deuterium isotope effects on the 13 C chemical shifts for Schiff base Noxides 1-4 and for the parent Schiff bases 1a-4a.…”
mentioning
confidence: 99%